ANALISIS KESESUAIAN PENERAPAN SISTEM PROTEKSI KEBAKARAN, SARANA PENYELAMATAN JIWA, DAN PENGORGANISASIAN PADA RUMAH SAKIT DR. SUYOTO TAHUN 2022 - Putik Novatri, (2022)
In 2019 dr. Suyoto Hospital experienced a fire caused by a short circuit of electric current. Potential fire hazards in dr. Suyoto Hospital is sourced from the use of fuel oil, LPG (Liquefied Petroleum Gas) and medical gas cylinders, flammable B3 (Hazardous and Toxic Materials), and electrical installations. The purpose of this study was to analyze the suitability of the application of fire protection systems, life-saving facilities, and organizing in dr. Suyoto Hospital compared to Permen PU No. 26/PRT/M/2008, Permen PU No. 20/PRT/M/2009, SNI (Indonesian National Standard), and international standard NFPA 101 (National Fire Protection Association 101). The study design used in this study is descriptive with a qualitative approach. The results of this study showed that the average suitability level of active fire protection systems was 83.38%, passive fire protection systems were 66.07%, life-saving facilities were 77.31%, and organizing was 100%. Thebest thing is that dr. Suyoto Hospital provides instructions for repairs to all hydrants and fire extinguishers, pays attention to the location of the fire extinguisher placement and pays attention to the use of fireproof doors, provides a clear track line along the access of the excit, makes SOPs (Standard Operating Procedures) and makes documents on the results of inspection, testing, and maintenance.